BATANG ARAU RIVER REVITALIZATION POLICY IN PADANG CITY - zuniva, Atifa Awdia Ramadani (Communale Journal, 2023)
Rapid population growth is different from the availability of clean water. In addition, water availability is also influenced by natural factors due to the dry season. Water purification problems often occur in urban and rural areas due to a lack of services to distribute water purification installations. Almost all islands in Java and Sumatra are experiencing a water crisis, such as the Batang Arau river in the city of Padang. The issues raised are related to how the local government's policy revitalizes the Batang Arau River, which is contaminated by garbage, household, and industrial waste. Revitalization efforts from the government and related agencies still need to improve in the form of budgets and a need for more public and business awareness about river cleanliness. It is necessary to establish an institution that has legality and deals explicitly with watershed pollution as well as possible—changing the lifestyle of people related to the river by providing counseling and knowledge to manage waste and not throw it into the river and to care more about the surrounding environment. With its own interests, the government needs to pay more attention to the environmental impacts of these interests, especially those related to river conservation.